Pengaruh Keterlibatan Kerja Terhadap Kinerja Pegawai yang Dimediasi oleh Kepuasan Kerja - Dwi Lestari, Kadek Intan; Kusyana, Dewa Nyoman Benni (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to establish how work engagement impacts employee performance through the mediator of job satisfaction. The study occurred at the Denpasar City Regional Secretariat Office, where 166 employees have civil servant status. Every individual in the population participated as research subjects through the census technique. Data was amassed through the use of both interviews and questionnaires. The data measurement scale employs a Likert scale consisting of five answer options. Validity and reliability tests were conducted to assess the instrument. The method of data analysis employed is path analysis with the utilization of SPSS software. In this study, 83 percent of the participants responded or 138 individuals took part as research subjects. The analysis shows that work involvement positively impacts employee performance and job satisfaction, while job satisfaction also positively affects employee performance. The findings of the Sobel test indicate that job satisfaction is a mediator between work involvement and employee performance.